The environment as part of the architectural curricula in the University of Minho - Mendonça, Paulo (2011)
This paper tries to identify and characterize the places among the studies curricula of the Architecture graduation program at the University of Minho, where the environment appears as a major concern. Knowing that environmental aspects should always be considered as an integrated part of sustainability concerns in general, environmental issues in the University of Minho’s graduation are integrated in a Sustainability Module, composed by 3 Curricular Units: a “Studio – Sustainability”, a “Seminar - Sustainability” and a “Compulsory – Indoor Environmental Quality”. This Module happens in the first semester of the 4th year, integrated on the “Construction and Technology” scientific area, offered to approximately 1/3 of the students. The recent experience about the work in this module, that started just two years ago, is reported here.